(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Class tardiness is defined as students not attending lecture on time and not being present in the time set. Tardiness in PUP Lopez is rampant among students attending first period or early morning classes. Thus, the study aimed to determine the reasons for student’s tardiness. It also aimed to lessen the tardiness among students through the use of “Quiz Mania” where quizzes were given to students having a 7:30 am classes. It is an action research which employed both descriptive and experimental research design. For the descriptive part, survey questionnaire was used which focused on the root cause of their tardiness in school. While, experimental part focused on the use of Quiz Mania. For the root cause of tardiness, students become late because of the distance of the school from their house, they are doing other work and because of not being interested with the lesson. But, usually, in order to avoid that, teachers get the attendance on the start of their class. The results also revealed that the use of “Quiz Mania” significantly reduced tardiness (p < .05) in students attending the early morning classes. Thus, could be an effective tool to lessen or completely eliminate tardiness in the campus.